Lithium ion battery
By adding specific compounds to the non-aqueous electrolyte of lithium-ion batteries and controlling the area ratio of O1s peak to F1s peak on the negative electrode surface, the problem of unstable film formation quality of SEI film is solved, and the battery is excellent long cycle stability and cycle life extension is achieved.
Patent Information
- Application Number
- CN202510119875.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2045-01-25
AI Technical Summary
The film formation quality of the SEI film on the negative electrode surface of the existing lithium-ion battery is unstable, resulting in an increase in impedance and a decrease in capacity during the charge and discharge cycle.
The compound shown in Structural Formula 1 is added as an additive to the nonaqueous electrolyte, and the ratio Y of the area of the O1s peak and the F1s peak on the negative electrode surface was tested by an X-ray photoelectron spectrometer to ensure that it is within the range of 0.3 to 0.6, so as to regulate the proportion of inorganic components of the SEI film.
By optimizing the ratio of Li2O and LiF components of the SEI film, the long cycle stability of the lithium-ion battery is significantly improved, the occurrence of interface side reactions is reduced, and the cycle life of the battery is extended.
Smart Images

Figure CN119560637A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage electronic components, and in particular to a lithium ion battery. Background Art
[0002] As the application technology of secondary batteries gradually matures, the market demand for electric vehicles and large-scale energy storage has exploded. It is understood that major manufacturers have mastered the key technologies to achieve more than 10,000 charge and discharge cycles of batteries, and are gradually moving towards the long-term goals of higher energy density, longer cycle life, greater safety and reliability. From a technical principle perspective, the core of lithium-ion battery long cycle technology lies in adjusting and optimizing the electrochemical stability of the solid electrolyte interface (SEI) through electrolyte design.
[0003] The underlying logic of an excellent SEI film is its chemical composition and distribution model. Existing SEI films formed by different additives have large differences in composition, and at the same time, there are also large differences in the stability of their film quality. Unstable SEI films will rupture and continue to repair and thicken during the charge and discharge cycle, which will lead to an increase in battery impedance and a decrease in capacity. How to regulate the SEI film composition to obtain a stable SEI film is an urgent problem to be solved. Summary of the invention
[0004] Aiming at the problem of unstable film-forming quality of SEI film on negative electrode surface in existing lithium ion batteries, the present invention provides a lithium ion battery.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the non-aqueous electrolyte comprises a non-aqueous organic solvent, an electrolyte salt and an additive, wherein the additive comprises a compound shown in structural formula 1: ; wherein n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, substituted or unsubstituted C2-C12 ether, and R1, R2 are not hydrogen at the same time, R1 and R2 may be connected to each other to form a ring or not; R3 is selected from substituted or unsubstituted C1-C12 alkylene, substituted or unsubstituted C2-12 alkenylene, substituted or unsubstituted C2-12 alkynylene, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; when R1, R2, and R3 are substituted, the substituent is alkoxy, hydroxyl, acyl, ester, cyano or halogen; The negative electrode surface was tested by X-ray photoelectron spectrometer: an Ar ion gun was used for etching at a speed of 10 nm / min and an etching power of 1 kV; the etching time was 5 min, and the peak at the binding energy position of 528 ± 1.0 eV was used as the O 1s The peak at the binding energy position of 685±1.0 eV is taken as F 1s Peak, O 1s Peak and F 1s The peak area ratio Y is 0.3~0.6.
[0006] Optionally, in the compound represented by the structural formula 1, R1 is selected from hydrogen, and R2 is selected from , substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl.
[0007] Optionally, in the compound shown in structural formula 1, R1 and R2 are each independently selected from a substituted or unsubstituted C1-C12 alkyl, a substituted or unsubstituted C2-C12 alkenyl, a substituted or unsubstituted C2-C12 alkynyl, or a substituted or unsubstituted C6-C20 aryl.
[0008] Optionally, in the compound represented by structural formula 1, R1 is selected from R2 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
[0009] Optionally, in the compound represented by structural formula 1, R1 is selected from , where R 12 R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 13 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl.
[0010] Optionally, the compound represented by structural formula 1 includes one or more of the following compounds: .
[0011] Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the mass content of the compound represented by Structural Formula 1 is 10 ppm to 1000 ppm.
[0012] Optionally, the non-aqueous electrolyte does not include a polymerizable monomer and / or a prepolymer obtained by polymerizing a polymerizable monomer.
[0013] Optionally, the additive further comprises at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a nitrile compound, a lithium salt additive or an alkane compound; and / or The cyclic sulfate ester compound includes at least one of vinyl sulfate, propylene sulfate and methyl vinyl sulfate; and / or The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1,3-propylene sultone and methylene disulfonate; and / or The cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate, methylene carbonate or the compound shown in structural formula 2: ; In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or The phosphate compound includes at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate or the compound shown in structural formula 3: ; In the structural formula 3, R 31 , R 32 , R 33Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, a C6-C12 aryl group, a C6-C12 halogenated aryl group, a -Si(C m H 2m+1 )3, m is a natural number from 1 to 3; and / or The nitrile compound comprises at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile; and / or The lithium salt additive includes at least one of lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium tetrafluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylsulfonyl imide, lithium bispentafluoroethylsulfonyl imide, lithium trifluoromethanesulfonate, lithium monofluorosulfonate, lithium trioxalate phosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium dicyanamide or a lower aliphatic lithium carboxylate having 4 or less carbon atoms; and / or The alkane compound includes at least one of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane and perfluoro(ethylcyclohexane).
[0014] Optionally, the negative electrode includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes one or more of soft carbon, hard carbon, artificial graphite, natural graphite, intermediate phase microcarbon beads, silicon, silicon oxides, silicon-carbon composites, metallic lithium or lithium titanate.
[0015] According to the lithium ion battery provided by the present invention, the compound shown in structural formula 1 is added to the non-aqueous electrolyte as an additive, and the peroxide group -OO- can provide [O] to promote the increase of Li2O component in SEI. In addition, the inventors have found through a large number of studies that in a battery system with the compound shown in structural formula 1 added, when the lithium ion battery meets the O detected by the negative electrode 1s Peak and F 1sWhen the peak area ratio Y is between 0.3 and 0.6, the inorganic components of SEI have an appropriate Li2O component and LiF component composition ratio, which can play an excellent protective role on the lithium-inserted negative electrode, reduce the occurrence of interface side reactions, and thus obtain excellent long-cycle stability. However, when the Y value is less than 0.3, the Li2O content is low, the lithium ion diffusion barrier is high, and the interface film impedance increases, which is not conducive to battery rate discharge; when the Y value is greater than 0.6, the LiF content is low, and the SEI film interface formed is relatively loose, resulting in increased side reactions, causing accelerated consumption of solvents and additives, and deteriorating the battery cycle life. DETAILED DESCRIPTION
[0016] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0017] An embodiment of the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the non-aqueous electrolyte comprises a non-aqueous organic solvent, an electrolyte salt and an additive, wherein the additive comprises a compound shown in Structural Formula 1; ; wherein n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, substituted or unsubstituted C2-C12 ether, and R1, R2 are not hydrogen at the same time, R1 and R2 may be connected to each other to form a ring or not; R3 is selected from substituted or unsubstituted C1-C12 alkylene, substituted or unsubstituted C2-12 alkenylene, substituted or unsubstituted C2-12 alkynylene, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; when R1, R2, and R3 are substituted, the substituent is alkoxy, hydroxyl, acyl, ester, cyano or halogen; The negative electrode surface was tested by X-ray photoelectron spectrometer: an Ar ion gun was used for etching at a speed of 10 nm / min and an etching power of 1 kV; the etching time was 5 min, and the peak at the binding energy position of 528 ± 1.0 eV was used as the O 1s The peak at the binding energy position of 685±1.0 eV is taken as F 1s Peak, O 1s Peak and F 1s The peak area ratio Y is 0.3~0.6.
[0018] According to the lithium ion battery provided by the present invention, the compound shown in structural formula 1 is added to the non-aqueous electrolyte as an additive, and the peroxide group -OO- can provide [O] to promote the increase of Li2O component in SEI. In addition, the inventors have found through a large number of studies that in a battery system with the compound shown in structural formula 1 added, when the lithium ion battery meets the O detected by the negative electrode 1s Peak and F 1s When the peak intensity ratio Y is between 0.3 and 0.6, the inorganic components of SEI have an appropriate Li2O component and LiF component composition ratio, which can play an excellent protective role on the lithium-inserted negative electrode, reduce the occurrence of interface side reactions, and thus obtain excellent long-cycle stability. However, when the Y value is less than 0.3, the Li2O content is low, the lithium ion diffusion barrier is high, and the interface film impedance increases, which is not conducive to battery rate discharge; when the Y value is greater than 0.6, the LiF content is low, and the SEI film interface formed is relatively loose, resulting in increased side reactions, causing accelerated consumption of solvents and additives, and deteriorating the battery cycle life.
[0019] In the description of the present invention, the term "C1-C12 alkyl" includes straight-chain alkyl, branched-chain alkyl and cycloalkyl. Similarly, the term "C2-C12 alkenyl" includes straight-chain alkenyl, branched-chain alkenyl and cycloalkenyl. The term "C2-C12 alkynyl" includes straight-chain alkynyl, branched-chain alkynyl and cycloalkynyl. The term "C1-C12 alkylene" includes straight-chain alkylene, branched-chain alkylene and cycloalkylene. The term "C2-C12 alkenylene" includes straight-chain alkenylene, branched-chain alkenylene and cycloalkenylene. The term "C2-C12 alkynylene" includes straight-chain alkynylene, branched-chain alkynylene and cycloalkynylene.
[0020] In the description of the present invention, the term "C1-C12 acyl group" should be understood in a broad sense. Specifically, it can be understood that a single or multiple carbon atoms in a C1-C12 alkyl group are replaced by a carbonyl group. The position of the substituted carbon atom is not particularly limited. In a preferred embodiment, the C1-C12 acyl group is selected from , where R 14 is selected from a single bond or a C1-C11 alkyl group, R 15 An alkyl group selected from C1-C11.
[0021] In the description of the present invention, the term "C2-C12 alkoxy acyl" should be understood in a broad sense. Specifically, it can be understood that a single or multiple carbon atoms in a C2-C12 alkyl group are replaced by an ester group. The position of the substituted carbon atom is not particularly limited. In a preferred embodiment, the C2-C12 alkoxyacyl group is selected from , where R 16is selected from a single bond or a C1-C11 alkyl group, R 17 An alkyl group selected from C1-C11.
[0022] In the description of the present invention, the term "C2-C12 ether group" should be understood in a broad sense. Specifically, it can be understood as a C2-C12 alkyl group connecting two adjacent carbon atoms. The number of oxygen atoms in the obtained group may be single or multiple.
[0023] In some embodiments, in the compound represented by the structural formula 1, R1 is selected from hydrogen, R2 is selected from , substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl.
[0024] At this time, the compound shown in the structural formula 1 is a hydroperoxide or an organic peracid. When the compound shown in the structural formula 1 is a hydroperoxide or an organic peracid, it has a higher oxygen content, which can remove reducing impurities in the electrolyte in advance, reduce the amount of gas produced during formation, improve the first coulomb efficiency, and increase the initial discharge capacity of the secondary battery.
[0025] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0026] In some embodiments, in the compound represented by structural formula 1, R1 and R2 are each independently selected from a substituted or unsubstituted C1-C12 alkyl, a substituted or unsubstituted C2-C12 alkenyl, a substituted or unsubstituted C2-C12 alkynyl, or a substituted or unsubstituted C6-C20 aryl.
[0027] At this time, the compound shown in the structural formula 1 is a dialkyl peroxide. When the compound shown in the structural formula 1 is a dialkyl peroxide, the co-embedding of solvent molecules can be suppressed, thereby improving the interface compatibility between the electrolyte and the negative electrode.
[0028] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0029] In some embodiments, in the compound represented by the structural formula 1, R1 is selected from R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
[0030] In some embodiments, in the compound represented by the structural formula 1, R1 is selected from ; R2 is selected from , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
[0031] At this time, the compound shown in the structural formula 1 is a diacyl peroxide. When the compound shown in the structural formula 1 is a diacyl peroxide, in addition to having the characteristics of improving the battery cycle life, it can also decompose to form inert carbon dioxide to dilute the explosion limit of the combustible gas when the battery is thermally runaway, which is beneficial to improving the battery safety performance.
[0032] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0033] In some embodiments, in the compound represented by the structural formula 1, R1 is selected from R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
[0034] At this time, the compound shown in the structural formula 1 is a peroxy acid ester. When the compound shown in the structural formula 1 is a peroxy acid ester, the wettability of the electrolyte to the electrode can be improved, the ohmic internal resistance of the battery can be reduced, and the discharge performance of the battery can be improved.
[0035] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0036] In some embodiments, in the compound represented by the structural formula 1, R1 is selected from , where R 12 R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 13 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl.
[0037] At this time, the compound shown in the structural formula 1 is a peroxycarbonate or a peroxydicarbonate. When the compound shown in the structural formula 1 is a peroxycarbonate or a peroxydicarbonate, it has the effect of promoting the solvation of lithium ions and improving the lithium diffusion performance inside the battery.
[0038] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0039] In some embodiments, the compound represented by structural formula 1 includes one or more of the following compounds: .
[0040] In a preferred embodiment, O 1s Peak and F 1s The peak area ratio Y is 0.4~0.5.
[0041] After lithium-ion batteries undergo the film-forming process of formation-aging-capacity separation, the non-aqueous electrolyte forms an organic-inorganic hybrid solid electrolyte interface film (SEI) at the solid-liquid interface of the negative electrode material. Li2O and LiF are two key inorganic components. LiF has a more critical influence on the protection of the SEI film, while Li2O has a lower lithium ion diffusion barrier and relatively high ionic conductivity. Increasing the Li2O component is beneficial to improving the coulomb efficiency and cycle life. In the XPS test of the SEI film on the negative electrode surface, the effective component corresponding to the O1s peak with a binding energy of 528±1.0eV is Li2O, and the effective component corresponding to the F1s peak with a binding energy of 685±1.0eV is LiF. When O 1s Peak and F 1s When the peak area ratio Y is within the above range, Li2O and LiF play a role in protecting the electrolyte from decomposition in an appropriate ratio.
[0042] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass content of the compound represented by Structural Formula 1 is 10 ppm to 1000 ppm.
[0043] In a specific embodiment, based on the total mass of the non-aqueous electrolyte as 100%, the mass content of the compound represented by the structural formula 1 can be 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 110ppm, 120ppm, 130ppm, 140ppm, 150ppm, 160ppm, 170ppm, 180ppm, 190ppm, 200ppm, 210ppm, 220ppm, 230ppm m, 240ppm, 250ppm, 270ppm, 290ppm, 300ppm, 310ppm, 320ppm, 330ppm, 340ppm, 350ppm, 370ppm, 390ppm, 400ppm, 410ppm, 420ppm, 430ppm, 440ppm, 450ppm, 470ppm, 490ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm or a range consisting of any two of these values.
[0044] In a preferred embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the mass content of the compound represented by Structural Formula 1 is 20 ppm to 500 ppm.
[0045] The content of the compound shown in structural formula 1 in the non-aqueous electrolyte will affect the relative content of Li2O and LiF components in the SEI film. When the content of the compound shown in structural formula 1 in the non-aqueous electrolyte is too low, the Li2O content in the SEI film will decrease, thereby increasing the negative electrode interface impedance. When the content of the compound shown in structural formula 1 in the non-aqueous electrolyte is too high, O 1s Peak and F 1s The increase of the area ratio Y of the peaks can easily lead to loose interface of the SEI film, resulting in an increase in the interface side reactions. However, it should be noted that the content of the compound shown in structural formula 1 does not affect the O 1s Peak and F 1s The only factor that affects the area ratio Y of the peaks is, for example, the wettability of the non-aqueous electrolyte to the negative electrode material layer affects the formation of the negative electrode solid electrolyte membrane. Under different compaction densities, the ratio of Li2O and LiF components in the obtained negative electrode solid electrolyte membrane is different; for example, the composition of the non-aqueous electrolyte, additives or impurities, etc., will cause changes in the components of the negative electrode SEI film; furthermore, the formation conditions of the lithium-ion battery will also affect the content ratio of different components in the SEI film. For example, adding a small amount of fluoroethylene carbonate to the non-aqueous electrolyte can promote the SEI to generate more LiF. For example, increasing the current density during the formation of the lithium-ion battery can induce the additive to undergo a two-electron reaction to form more Li2O. Furthermore, by controlling O 1s Peak and F 1s The peak area ratio Y and the content of the compound shown in structural formula 1 can combine the combined effects of the two on the performance of lithium-ion batteries to achieve a synergistic improvement effect.
[0046] In some embodiments, the formation conditions of the lithium-ion battery are: a formation temperature of 40-50° C., a formation pressure of 3-6 kg / cc, and a charging current of 0.05-0.2C.
[0047] It should be emphasized that the non-aqueous electrolyte provided in the present application is not a precursor of a gel electrolyte or a solid electrolyte, nor is it suitable as a precursor of a gel electrolyte or a solid electrolyte. The reason is that the improvement of the electrochemical performance of the secondary battery in the present application depends on the regulation of the SEI film composition by the compound shown in Structural Formula 1 during the battery charge and discharge formation process, and the continuous effect of the compound shown in Structural Formula 1 remaining in the electrolyte on lithium ion conduction during the long-term cycle of the battery. As a precursor of a gel electrolyte or a solid electrolyte, there is a polymerization operation to form a gel electrolyte before the battery charge and discharge formation. In the polymerization operation, the compound shown in Structural Formula 1 reacts with the polymerizable monomer as an initiator, resulting in the consumption of the compound shown in Structural Formula 1, and thus cannot play a corresponding role in the charge and discharge formation and the battery charge and discharge cycle process.
[0048] In some embodiments, the non-aqueous electrolyte does not include a polymerizable monomer and / or a prepolymer obtained by polymerizing a polymerizable monomer.
[0049] In some embodiments, the polymerizable monomers include one or more of acrylate monomers (such as methyl acrylate, ethyl acrylate, butyl acrylate), acrylamide monomers (such as acrylamide, N,N'-methylenebisacrylamide), vinyl compound monomers (such as polyvinyl alcohol, vinyl pyrrolidone, vinyl imidazole), epoxy resin monomers (such as bisphenol A epoxy resin), polyethylene oxide monomers, polyacrylonitrile monomers, and siloxane monomers.
[0050] In some embodiments, the non-aqueous electrolyte does not undergo polymerization reaction under light or heating conditions.
[0051] In some embodiments, the non-aqueous electrolyte is in liquid state after formation.
[0052] In some embodiments, the viscosity of the non-aqueous electrolyte is 2 mPa·s to 10 mPa·s.
[0053] In some embodiments, the additive further comprises at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a nitrile compound, a lithium salt additive or an alkane compound.
[0054] In some embodiments, the cyclic sulfate ester compound includes at least one of vinyl sulfate, propylene sulfate, and methyl vinyl sulfate.
[0055] In some embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1,3-propene sultone, and methylene disulfonate.
[0056] In some embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, or a compound shown in Structural Formula 2: ; In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group.
[0057] In some embodiments, the phosphate compound includes a compound shown in Structural Formula 3: ; In the structural formula 3, R 31 , R 32 , R 33 Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, a C6-C12 aryl group, a C6-C12 halogenated aryl group, a -Si(C m H 2m+1 )3, m is a natural number from 1 to 3.
[0058] In some embodiments, the nitrile compound includes at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, and sebacononitrile.
[0059] In some embodiments, the lithium salt additive includes at least one of lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium tetrafluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylsulfonyl imide, lithium bispentafluoroethylsulfonyl imide, lithium trifluoromethanesulfonate, lithium monofluorosulfonate, lithium trioxalate phosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium dicyanamide, or a lower aliphatic lithium carboxylate having 4 or less carbon atoms.
[0060] In some embodiments, the alkane compound includes at least one of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane and perfluoro(ethylcyclohexane).
[0061] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the total content of the additive is 1% to 12%.
[0062] In some embodiments, the mass content of any one of the optional substances in the additive is 0.01% to 10%. Specifically, the content of any one of the optional substances in the additive can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10% or a range consisting of any two of these values.
[0063] In some embodiments, the non-aqueous organic solvent includes at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent, and a sulfone solvent.
[0064] In some embodiments, the ether solvent includes a cyclic ether or a chain ether, preferably a chain ether with 3 to 10 carbon atoms and a cyclic ether with 3 to 6 carbon atoms. The cyclic ether may be, but is not limited to, at least one of 1,3-dioxolane, 1,4-dioxane, crown ether, tetrahydrofuran, 2-methyltetrahydrofuran, and 2-trifluoromethyltetrahydrofuran; the chain ether may be, but is not limited to, dimethoxymethane, diethoxymethane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether. Since the chain ether has a high solvation ability with lithium ions and can improve ion dissociation, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane, which have low viscosity and can impart high ionic conductivity, are particularly preferred. Ether compounds can be used alone or in any combination and ratio. The content of the ether compound is not particularly limited and is arbitrary within the range that does not significantly damage the effect of the high-density lithium-ion battery of the present invention. The volume ratio is usually 1% or more, preferably 2% or more, and more preferably 3% or more, based on the volume ratio of the non-aqueous solvent being 100%. In addition, the volume ratio is usually 30% or less, preferably 25% or less, and more preferably 20% or less.
[0065] In some embodiments, the nitrile solvent may specifically be but is not limited to at least one of acetonitrile, glutaronitrile, and malononitrile.
[0066] In some embodiments, the carbonate solvent includes a cyclic carbonate or a chain carbonate, and the cyclic carbonate may be specifically but not limited to at least one of ethylene carbonate, propylene carbonate, γ-butyrolactone, and butylene carbonate; the chain carbonate may be specifically but not limited to at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate. The content of the cyclic carbonate is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention, but when one is used alone, the lower limit of its content is usually 3% or more by volume, preferably 5% or more by volume, relative to the total amount of solvent in the non-aqueous electrolyte. By setting this range, the conductivity is reduced due to the reduction in the dielectric constant of the non-aqueous electrolyte, and it is easy to make the large current discharge characteristics of the non-aqueous electrolyte battery, the stability relative to the negative electrode, and the cycle characteristics reach a good range. In addition, the upper limit is usually less than 90% by volume, preferably less than 85% by volume, and more preferably less than 80% by volume. By setting this range, the oxidation / reduction resistance of the non-aqueous electrolyte can be improved, thereby helping to improve the stability during high temperature storage. The content of linear carbonate is not particularly limited, and relative to the total amount of solvent of nonaqueous electrolytic solution, is usually more than 15% by volume, preferably more than 20% by volume, more preferably more than 25% by volume. In addition, usually below 90% by volume, preferably below 85% by volume, more preferably below 80% by volume. By making the content of linear carbonate in above-mentioned scope, easily make the viscosity of nonaqueous electrolytic solution reach appropriate range, suppress the reduction of ionic conductivity, and then contribute to make the output characteristics of nonaqueous electrolyte battery reach good scope. When using two or more linear carbonates in combination, make the total amount of linear carbonate satisfy above-mentioned scope.
[0067] In certain embodiments, it is also possible to preferably use chain carbonates with fluorine atoms (hereinafter referred to as "fluorinated chain carbonates"). The number of fluorine atoms possessed by the fluorinated chain carbonate is not particularly limited as long as it is more than 1, but is generally less than 6, preferably less than 4. When the fluorinated chain carbonate has a plurality of fluorine atoms, these fluorine atoms can be bonded to the same carbon or to different carbons. As the fluorinated chain carbonate, fluorinated dimethyl carbonate derivatives, fluorinated ethyl methyl carbonate derivatives, fluorinated diethyl carbonate derivatives, etc. can be listed.
[0068] Carboxylate solvents include cyclic carboxylate and / or chain carbonate. Examples of cyclic carboxylate include at least one of γ-butyrolactone, γ-valerolactone, and δ-valerolactone. Examples of chain carbonate include at least one of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, propyl propionate, and butyl propionate.
[0069] In some embodiments, the sulfone solvent includes a cyclic sulfone and a chain sulfone. Preferably, in the case of a cyclic sulfone, it is usually a compound with 3 to 6 carbon atoms, preferably 3 to 5 carbon atoms, and in the case of a chain sulfone, it is usually a compound with 2 to 6 carbon atoms, preferably 2 to 5 carbon atoms. The content of the sulfone solvent is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention. Relative to the total amount of solvent of the non-aqueous electrolyte, the volume ratio is usually 0.3% or more, preferably 0.5% or more, and more preferably 1% or more. In addition, the volume ratio is usually 40% or less, preferably 35% or less, and more preferably 30% or less. In the case of using two or more sulfone solvents in combination, the total amount of the sulfone solvent is sufficient to meet the above range. When the content of the sulfone solvent is within the above range, a non-aqueous electrolyte with excellent high temperature storage stability tends to be obtained.
[0070] In a preferred embodiment, the non-aqueous organic solvent comprises a mixture of cyclic carbonate and linear carbonate.
[0071] In some embodiments, the electrolyte salt is selected from lithium salts, including LiPF6, LiBOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiClO4, LiAlCl4, LiCF3SO3, LiSO3F, Li2B 10 Cl 10 , lithium chloroborane, lithium trioxalophosphate, a lithium lower aliphatic carboxylate having 4 or less carbon atoms, or at least one of lithium tetraphenylborate.
[0072] In some embodiments, the concentration of the lithium salt in the non-aqueous electrolyte is 0.1 mol / L to 4 mol / L. In a preferred embodiment, the concentration of the lithium salt in the non-aqueous electrolyte is 0.5 mol / L to 2.5 mol / L. Specifically, in the non-aqueous electrolyte, the concentration of the lithium salt can be 0.5mol / L, 0.55mol / L, 0.6mol / L, 0.65mol / L, 0.7mol / L, 0.8mol / L, 0.85mol / L, 0.9mol / L, 0.95mol / L, 1.0mol / L, 1.1mol / L, 1.15mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.45mol / L, 1.5mol / L, 1.6mol / L, 1.7mol / L, 1.8mol / L, 1.9mol / L, 2.0mol / L, 2.1mol / L, 2.2mol / L, 2.3mol / L, 2.4mol / L, 2.5mol / L or a range consisting of any two of these values.
[0073] In some embodiments, the positive electrode comprises a positive electrode material layer, the positive electrode material layer comprises a positive electrode active material, and the positive electrode active material is selected from LiFe 1-x’ M' x’ PO4、LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-z At least one of O2, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.
[0074] In a preferred embodiment, the positive electrode active material is selected from LiFe 1-x’ M' x’ PO4, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1.
[0075] In a more preferred embodiment, the positive electrode active material is selected from LiFe 1-x’ Mn x’ PO4, where 0≤x'≤0.5.
[0076] In some embodiments, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductor, and the positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer.
[0077] The positive electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.
[0078] The positive electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0079] In some embodiments, the positive electrode current collector includes a metal material that can conduct electrons. Preferably, the positive electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.
[0080] In some embodiments, the negative electrode includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, and a lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy.
[0081] In a more preferred embodiment, the negative electrode active material includes at least one of graphite, hard carbon, soft carbon, graphene, and silicon-carbon composite materials.
[0082] In some embodiments, the silicon material is one or more of silicon nanoparticles, silicon nanowires, silicon nanotubes, silicon thin films, and porous silicon.
[0083] In some embodiments, the negative electrode further comprises a negative electrode current collector, and the negative electrode material layer covers the surface of the negative electrode current collector. The negative electrode current collector comprises a metal material that can conduct electrons, preferably, the negative electrode current collector comprises at least one of Al, Ni, tin, copper, and stainless steel, and in a more preferred embodiment, the negative electrode current collector is selected from copper foil.
[0084] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are blended to obtain the negative electrode material layer.
[0085] The negative electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.
[0086] The negative electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0087] In some embodiments, the secondary battery further includes a separator, and the separator is located between the positive electrode and the negative electrode.
[0088] The diaphragm may be an existing conventional diaphragm, such as a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.
[0089] Example The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0090] Example 1 This example is used to illustrate the preparation method of the lithium ion battery disclosed in the present invention, which includes the following steps: (1) Preparation of non-aqueous electrolyte: The solvents ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 5:2:5:8, and then lithium hexafluorophosphate (LiPF6) is added as an electrolyte salt and the additives shown in Table 1. After oscillation and homogenization, the mixture is filtered and allowed to stand for use; the content of lithium hexafluorophosphate in the non-aqueous electrolyte is 1 mol / L, and the content of each additive is as shown in Table 1.
[0091] (2) Battery filling and formation: In a glove box with a water content of <10ppm and an oxygen content of <50ppm, the prepared electrolyte was injected into the lithium iron phosphate / graphite dry battery cell, maintained at a vacuum of 20 kPa for 10min, and the packaged battery was aged at 45°C for 48h. Then, the formation was performed as shown in Table 1. After the formation, the vacuum was evacuated and sealed, and then further charged to 3.65V at a constant current of 0.2C, and charged to 0.03C at a constant voltage, and then discharged to 2.5V at a constant current of 0.2C to obtain a lithium-ion battery.
[0092] Embodiments 2 to 24 Examples 2 to 24 are used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and include most of the operation steps in Example 1, except that: The types and contents of the additives and the formation conditions in Examples 2 to 24 are shown in Table 1.
[0093] Comparative Examples 1 to 8 Comparative Examples 1 to 8 are used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and include most of the operation steps in Example 1, except that: The types and contents of additives and the formation conditions in Comparative Examples 1 to 8 are shown in Table 1.
[0094] Table 1
[0095] In Table 1, the formation conditions "45℃, 0.1C cc 60min, 3kg / cc; 45℃, 0.2C cc 90min, 5kg / cc" indicate that the formation is divided into two stages: the first stage: temperature 45℃, charging current 0.1C, charging time 60min, pressure 3kg / cc; the second stage: temperature 45℃, charging current 0.2C, charging time 90min, pressure 5kg / cc.
[0096] VC is vinylene carbonate, MMDS is methylene disulfonate, DTD is vinyl sulfate, PS is propane sultone, FPS is fluoropropane sultone, TVS is tetravinylsilane, SN is succinonitrile, FEC is fluoroethylene carbonate, HTCN is hexane trinitrile, ECH is ethylcyclohexane, and TBMPi is triphenyl phosphite.
[0097] Performance Testing 1. Negative electrode surface O 1s Peak and F 1s Peak area ratio test: The lithium-ion batteries prepared in the examples and comparative examples were disassembled in a glove box filled with argon to obtain negative electrode sheets. The obtained negative electrode sheets were cut into test samples of 8 mm × 8 mm in size, and soaked and cleaned with a low-boiling dimethyl carbonate (DMC) solvent for half an hour. After being completely dried, they were pasted on the XPS sample stage, with the surface of the negative electrode material layer facing away from the current collector facing upward. The samples were vacuum degassed, and then the sample stage was transferred to the X-ray photoelectron spectrometer (XPS) for measurement without being exposed to the atmosphere. The specific test conditions and steps are as follows: Ar ion gun etching was performed at a speed of 10 nm / min and an etching power of 1 kV; the etching time was 5 min, and the peak at the binding energy position of 528 ± 1.0 eV was used as the O 1s The peak at the binding energy position of 685±1.0 eV is taken as F 1s Peak, O 1s Peak and F 1s The peak area ratio is recorded in Table 1 2. Battery cycle test at room temperature: The divided battery is placed in a constant temperature environment of 25℃, and after a short period of rest, it is charged to 3.65V at a constant current and constant voltage of 1C, with a cut-off current of 0.05C. After a short period of rest, it is discharged to 2.5V at a constant current of 1.5C, and this charge and discharge cycle is repeated for 2000 cycles. The initial impedance of the battery and the impedance of the battery at the 2000th cycle are recorded, and the discharge capacity of each cycle is recorded; Capacity retention rate (%) = 2000th cycle discharge capacity / first cycle discharge capacity * 100%, and calculate the average value of parallel samples; Impedance growth rate (%) = (battery impedance at the 2000th cycle - battery initial impedance) / battery initial impedance * 100%.
[0098] (1) The test results obtained in Examples 1 to 10 and Comparative Examples 1 to 8 are shown in Table 2.
[0099] Table 2
[0100] It can be seen from the test results of Examples 1 to 10 and Comparative Examples 1 to 8 that in the battery system to which the compound represented by Structural Formula 1 is added, when the lithium-ion battery satisfies the additional condition that the intensity ratio Y of the O1s peak to the F1s peak detected at the negative electrode is between 0.3 and 0.6, the obtained lithium-ion battery has excellent long cycle stability, indicating that the inorganic component of the SEI film has an appropriate Li2O and LiF component composition ratio at this time, and cooperates with the compound represented by Structural Formula 1 to play an excellent protective role on the lithium-inserted negative electrode and reduce the occurrence of interface side reactions. When the Y value is less than 0.3, the Li2O content is less, the lithium ion diffusion energy barrier is higher, and the interface film impedance increases, which is not conducive to the rate discharge of the battery; when the Y value exceeds 0.6, the LiF content is less, and the formed SEI film interface is relatively loose, resulting in an increase in side reactions, causing accelerated consumption of solvents and additives, thereby deteriorating the cycle life of the battery.
[0101] At the same time, based on Examples 1 to 10, it can be seen that at low contents, as the content of the compound shown in Structural Formula 1 increases, the Y value gradually increases, indicating that the Li2O component in the SEI film gradually increases at this time. When the content of the compound shown in Structural Formula 1 reaches a certain amount, the effect on the Y value is not obvious. When the intensity ratio Y of the O1s peak to the F1s peak is controlled to be between 0.3 and 0.6, and the content of the compound shown in Structural Formula 1 is controlled to be between 20 and 500 ppm, the cycle performance of the lithium ion battery is improved most significantly. From the test results of Comparative Examples 2 to 5 and Comparative Examples 6 to 8, it can be seen that even under the condition that the content of the compound shown in Structural Formula 1 is appropriate, when other additives or formation conditions are changed to cause the intensity ratio Y of the O1s peak to the F1s peak of the negative electrode to be too large or too small, the compound shown in Structural Formula 1 will not be able to play the improvement effect on the lithium ion battery, indicating that in terms of improving the cycle performance of lithium ion batteries, the addition of the compound shown in Structural Formula 1 and the control of the intensity ratio Y of the O1s peak to the F1s peak of the negative electrode are both necessary.
[0102] (2) The test results obtained in Examples 4 and 11 to 16 are entered in Table 3.
[0103] Table 3
[0104] It can be seen from the test results of Examples 4 and 11 to 16 that in the battery system provided by the present invention, when the intensity ratio Y of the O1s peak to the F1s peak of the negative electrode satisfies 0.3 to 0.6, using different compounds represented by structural formula 1 as additives can significantly improve the cycle capacity retention rate of the lithium ion battery, and is also beneficial to reduce the cycle internal resistance, indicating that the battery system provided by the present invention is suitable for different types of compounds represented by structural formula 1, and the peroxide group -OO- shared by the compounds represented by different structural formulas 1 is related to the performance improvement of lithium ion batteries.
[0105] (3) The test results obtained in Examples 4 and 17 to 20 are entered in Table 4.
[0106] Table 4
[0107] It can be seen from the test results of Examples 4 and 17 to 20 that when the content of the compound represented by Structural Formula 1 is constant, adjusting the types and contents of other additives in the electrolyte system will cause the intensity ratio Y of the O1s peak to the F1s peak of the negative electrode to change, thereby affecting the cycle capacity retention rate and impedance growth rate of the lithium-ion battery, indicating that the intensity ratio Y of the O1s peak to the F1s peak of the negative electrode is not only affected by the content of the compound represented by Structural Formula 1, but also by the composition of other additives in the non-aqueous electrolyte.
[0108] (4) The test results obtained in Examples 4 and 21 to 24 are entered in Table 5.
[0109] Table 5
[0110] It can be seen from the test results of Examples 4 and 21 to 24 that when the content of the compound represented by Structural Formula 1 is constant, adjusting the formation conditions will cause the intensity ratio Y of the O1s peak to the F1s peak of the negative electrode to change, thereby affecting the cycle capacity retention rate and impedance growth rate of the lithium-ion battery, indicating that the intensity ratio Y of the O1s peak to the F1s peak of the negative electrode is not only affected by the content of the compound represented by Structural Formula 1, but also by the formation conditions.
[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: It includes a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the non-aqueous electrolyte includes a non-aqueous organic solvent, an electrolyte salt and an additive, and the additive includes a compound shown in structural formula 1: ; wherein n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, substituted or unsubstituted C2-C12 ether, and R1, R2 are not hydrogen at the same time, R1 and R2 may be connected to each other to form a ring or not; R3 is selected from substituted or unsubstituted C1-C12 alkylene, substituted or unsubstituted C2-12 alkenylene, substituted or unsubstituted C2-12 alkynylene, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; when R1, R2, and R3 are substituted, the substituent is alkoxy, hydroxyl, acyl, ester, cyano or halogen; The negative electrode surface was tested by X-ray photoelectron spectrometer: an Ar ion gun was used for etching at a speed of 10 nm / min and an etching power of 1 kV; the etching time was 5 min, and the peak at the binding energy position of 528 ± 1.0 eV was used as the O 1s The peak at the binding energy position of 685±1.0 eV is taken as F 1s Peak, O 1s Peak and F 1s The peak area ratio Y is 0.3~0.
6.
2. The lithium-ion battery according to claim 1, characterized in that In the compound represented by the structural formula 1, R1 is selected from hydrogen, R2 is selected from , substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl.
3. The lithium-ion battery according to claim 1, characterized in that In the compound represented by structural formula 1, R1 and R2 are each independently selected from a substituted or unsubstituted C1-C12 alkyl group, a substituted or unsubstituted C2-C12 alkenyl group, a substituted or unsubstituted C2-C12 alkynyl group, or a substituted or unsubstituted C6-C20 aryl group.
4. The lithium-ion battery according to claim 1, characterized in that: In the compound represented by the structural formula 1, R1 is selected from R2 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
5. The lithium-ion battery according to claim 1, characterized in that: In the compound represented by the structural formula 1, R1 is selected from , where R 12 R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 13 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl.
6. The lithium-ion battery according to claim 1, characterized in that The compound represented by the structural formula 1 includes one or more of the following compounds: 。 7. The lithium-ion battery according to claim 1, characterized in that: Based on the total mass of the non-aqueous electrolyte being 100%, the mass content of the compound represented by the structural formula 1 is 10 ppm to 1000 ppm.
8. The lithium-ion battery according to claim 1, characterized in that The non-aqueous electrolyte does not include a polymerizable monomer and / or a prepolymer obtained by polymerizing a polymerizable monomer.
9. The lithium-ion battery according to claim 1, characterized in that: The additive further comprises at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a nitrile compound, a lithium salt additive or an alkane compound; and / or The cyclic sulfate ester compound includes at least one of vinyl sulfate, propylene sulfate and methyl vinyl sulfate; and / or The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1,3-propylene sultone and methylene disulfonate; and / or The cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate, methylene carbonate or the compound shown in structural formula 2: ; In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or The phosphate compound includes a compound shown in structural formula 3: ; In the structural formula 3, R 31 , R 32 , R 33 Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, a C6-C12 aryl group, a C6-C12 halogenated aryl group, a -Si(C m H 2m+1 )3, m is a natural number from 1 to 3; and / or The nitrile compound comprises at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile; and / or The lithium salt additive includes at least one of lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium tetrafluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylsulfonyl imide, lithium bispentafluoroethylsulfonyl imide, lithium trifluoromethanesulfonate, lithium monofluorosulfonate, lithium trioxalate phosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium dicyanamide or a lower aliphatic lithium carboxylate having 4 or less carbon atoms; and / or The alkane compound includes at least one of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane and perfluoro(ethylcyclohexane).
10. The lithium ion battery according to claim 1, characterized in that: The negative electrode includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes one or more of soft carbon, hard carbon, artificial graphite, natural graphite, intermediate phase microcarbon beads, silicon, silicon oxides, silicon carbon composites, metallic lithium or lithium titanate.
Citation Information
Patent Citations
A making method for lithium ion secondary cell
CN101079509A
Electrochemical cells comprising electrolyte additives, and methods for making and using the same
CN104541388A
High-stability potato peptide emulsion and preparation method thereof
CN106962942A
Carbon black for batteries, coating liquid for batteries, positive electrode for nonaqueous batteries, and nonaqueous battery
CN111052468A
Lithium ion battery
CN115498268A